Upaya Pelestarian Lingkungan Desa Bongkasa Berdasarkan Ajaran Tri Hita Karana - Mariantika, Ni Putu; Nerawati, Ni Gusti Ayu Agung (Jayapangus Press, 2022)
Preservation of the village environment is very important to do as a form of maintaining a comfortable and healthy village environment for the continuity of community life in the future and in the long term. Preservation of the village environment is not only done in tourist villages. Preserving the environment is very important, this makes village communities in Bali, especially in Bongkasa Village, must have a good strategy in preserving the village environment. This study uses a qualitative research approach and type by utilizing literature study or literature study as the main technique in collecting information. Tri Hita Karana is three concepts used as an effort to preserve the environment of Bongkasa Village. These three concepts consist of parahyangan, which is a good relationship with God, such as cultivating flowers and fruit plants that can be used as a means of complementing ceremonies, celebrating the holy day of tumpek wariga as a form of expression of gratitude to God for all the abundance of crops, cleaning the sacred area / temple. Pawongan is a good relationship with fellow humans such as: mareresik, mutual cooperation to clean the village, and other menyama braya activities that can increase social interaction in an effort to protect and preserve the environment. Palemahan is a good relationship with the surrounding nature or environment, such as making subak irrigation, mareresik / cleaning the environment, Krida and Friday Clean, holding tree planting activities, and increasing the tourism sector based on natural beauty, by utilizing existing resources.